Determinan Non Performing Financing Perbankan Syariah: Perspektif Makro Ekonomi - Rachma Zannati; Hendryadi Hendryadi (LPMP Imperium, 2019)
Purpose- This study aims to examine the effect of macroeconomics on non-performing financing (NPF) of Islamic banking in Indonesia. Methods- Data were collected from 14 Sharia Commercial Banks (BUS) in the period 2014 - 2018, and analysis techniques used hierarchical linear regression. Findings- This study shows that macroeconomic does not have a significant effect on the NPF of Islamic banking. Research implications- this study can be used as a basis for subsequent research and preliminary information for Islamic banking management to manage NPF. The main contribution of this research is as an empirical reference regarding the debate about the power of Islamic banking in dealing with external conditions, especially macroeconomic, especially in Indonesia.